Obtención de un inóculo microbiano, proveniente de las descargas líquidas de la Universidad Politécnica Salesiana, Sede Quito-Campus Sur, y evaluación de su capacidad de degradación de la materia orgánica de dichas descargas a escala de laboratorio - Vargas Espín, Danny Fernando (2014)
This research studied the behavior of six native microbial inoculums obtained from the Universidad Politécnica Salesiana wastewater. The measure the COD and BOD5 from the contaminated water during the characterization of each isolated strains established the efficacy of treatment and the reduction of the organic matter in the degradation assays. It is necessary to understand that within the wastewater treatment, there is no a unique solution to reduce or completely eliminate all the pollution load for diversity and complexity of the processes and activities that generate it. A realistic vision is to progressively reduce the pollution load to reach the limits set by the national legislation Texto Unificado de Legislación Ambiental Secundario, Libro VI Anexo 1 and Ordenanza Municipal 0213 DM. Quito for discharges into water bodies. Of the 6 inocula that were investigated, the inoculum UPS1 reached values of reduction of organic matter expressed in terms of BOD5 and COD above 50% for both parameters. This value accomplished the limits set by environmental regulations cited above.